1962
DOI: 10.1161/01.res.11.3.450
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Alterations of Acute Pulmonary Thromboembolism

Abstract: A method is described of producing pulmonary embolism in the dog by the use of various-sized autologous clots made radiopaque. This method of experimental pulmonary embolism results in dilatation of the large- to small-sized pulmonary arteries and a consistent hemodynamic response in the pulmonary circulation, characterized by a marked rise in pulmonary arteriolar resistance with increased pulmonary arterial pressure but persistently normal pulmonary venous and "capillary" pressures. Data are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1965
1965
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Parmley and associates 8 reported pulmonary edema as the immediate cause of death in 8 of 30 dogs given autologous blood clot emboli.…”
mentioning
confidence: 99%
“…Parmley and associates 8 reported pulmonary edema as the immediate cause of death in 8 of 30 dogs given autologous blood clot emboli.…”
mentioning
confidence: 99%
“…While Souza et al found a significant relationship between the PVS and unilateral PTE, we found a significant relationship between the PVS and bilateral PTE. This may be due to the fact that PTE in the main pulmonary artery or bilateral PTE markedly increases pulmonary artery pressure and pulmonary vascular resistance . However, it does not seem possible to make more comments according to the retrospective analysis in which pulmonary artery pressure and resistance measurements could not be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in lung water from uneven obstruction of the pulmonary vasculature ("overperfusion pulmonary oedema") has been studied in animals with a variety of micro emboli,s and has been suggested as a contributing factor in the pulmonary oedema, sometimes seen in pulmonary thrombo-embolism. 9 ,!O The pathogenesis of the oedema may involve "overperfusion" and transmission of high pressures to the unobstructed vasculature, although the release of substances altering endothelial permeability has not been excluded. O'Kuda et al theorise that physical injury to the endotheliun by high velocity and high pressure flow in the patent pulmonary microcirculation may account for the permeability oedema seen.…”
Section: Discussionmentioning
confidence: 99%